2019
DOI: 10.1055/a-0938-3918
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness of endoscopic ultrasound-directed transgastric ERCP compared with device-assisted and laparoscopic-assisted ERCP in patients with Roux-en-Y anatomy

Abstract: Background Roux-en-Y gastric bypass (RYGB) surgery is the second most common weight loss surgery in the United States. Treatment of pancreaticobiliary disease in this patient population is challenging due to the altered anatomy, which limits the use of standard instruments and techniques. Both nonoperative and operative modalities are available to overcome these limitations, including device-assisted (DAE) endoscopic retrograde cholangiopancreatography (ERCP), laparoscopic-assisted (LA) ERCP, and endoscopic ul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(26 citation statements)
references
References 28 publications
0
26
0
Order By: Relevance
“…These figures compare favorably to LA-ERCP, for which published LOS varies (1.9 to 3.9 days [25,12,17,24]. In a recent analysis, EDGE was found to be more cost-effective than either LA-ERCP or BAE-ERCP [41]…”
Section: Accepted M Manuscriptmentioning
confidence: 88%
“…These figures compare favorably to LA-ERCP, for which published LOS varies (1.9 to 3.9 days [25,12,17,24]. In a recent analysis, EDGE was found to be more cost-effective than either LA-ERCP or BAE-ERCP [41]…”
Section: Accepted M Manuscriptmentioning
confidence: 88%
“…EDGE procedures were of shorter duration (73 minutes vs 184 minutes) and patients had a shorter hospital stay (0.8 days vs 2.65 days) (32). EDGE also appears to be a more cost effective modality (34). A retrospective multi-centred review of 30 patients in each arm of EDGE vs BE-ERCP found EDGE to have a statistically significantly higher success rate (100% vs 60%, p<.001), shorter procedure time (49.8 vs 90.7minutes p<.001), shorter length of stay (1 vs 10.5 days p =.02) with similar adverse event rates (10% vs 6.7%) (33).…”
Section: Discussionmentioning
confidence: 99%
“…In this report, we wish to demonstrate its feasibility and safety as a single-step pro-cedure. Moreover, despite the high cost of the Hot Axios system, in a comparison with other current alternative strategies for Roux-en-Y anastomosis, EDGE was shown to be the most cost-effective [5]. Thus, shortening the procedure into a single session should reduce even further the cost of patient management.…”
Section: E229mentioning
confidence: 99%